Community based intervention: Local village preparedness in prevention and control of COVID-19 - Muhamad Jauhar; Rasdiyanah Rasdiyanah; Lita Heni Kusumawardani; Utami Rachmawati; I Gusti Ayu Putu Desy Rohana (Journal of Community Empowerment for Health, 2021)
The COVID-19 pandemic has become a global concern since it has severely affected various aspects of life such as health, economy, society, culture, and religion. Community empowerment in breaking the chain of region-based COVID-19 spread is an effective approach that can be taken. This intervention is an important alternative measure to slow the morbidity and mortality of COVID-19 that continue to occur in Indonesia. This article aimed to describe the implementation of a community-based COVID-19 prevention program that was conducted among 280 families in six sub-districts in Brebes Regency from May to June 2020. The assessment used a questionnaire of COVID-19 transmission risk, with a total of 29 indicators developed based on references from the Indonesian Ministry of Health. The preliminary assessment of our program found several aspects that were related to the risk of COVID-19 transmission in the village and observed that there was insufficient public knowledge about COVID-19 including poor practice of health protocols and the negative stigma of society towards patients with COVID-19. The community-based program involved several activities, which namely consisted of program introduction, coordination with stakeholders, community assessments, group discussions, village community deliberations, health education about COVID-19 and 6 step hand washing, distribution of cloth masks, socialization of mask usage and care, socialization of pregnancy checks during the pandemic, provision of hand washing facilities in front of the house, activities evaluation, follow-up plans, and closings.  Furthermore, the aforementioned activities also used videos, posters, leaflets, WhatsApp, as well as Zoom Cloud Meetings as the media. The evaluation phase of the program showed a better understanding related to COVID-19 and health protocol practice in each region. Community empowerment and collaboration with health care facilities can be pursued as a frontline solution to tackle the transmission of COVID-19. Good support and active community participation can contribute to improve the public health status.